2005
DOI: 10.1097/01.ta.0000198364.50334.39
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Criteria for Temporary External Fixation in Risk-Adapted Damage Control Orthopedic Surgery of Femur Shaft Fractures in Multiple Trauma Patients: ???Evidence-Based Medicine??? versus ???Reality??? in the Trauma Registry of the German Trauma Society

Abstract: Clinical "reality" reflects the controversies of "scientific evidence" for FSFT after multiple trauma in Germany. Although decision making is currently based on unvalidated criteria, anatomic and physiologic injury severity appears to influence the choice of management concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 77 publications
(51 reference statements)
5
38
0
5
Order By: Relevance
“…In order to provide clinically relevant categories for treatment beyond a simple dichotomy at twelve or twenty-four hours, we chose five time periods a priori on the basis of commonly used cut-points from the literature 14,15,24 : t 0 (twelve hours or less), t 1 (more than twelve hours to twenty-four hours), t 2 (more than twenty-four hours to fortyeight hours), t 3 (more than forty-eight hours to 120 hours), and t 4 (more than 120 hours). While twenty-four hours is the most commonly used threshold before which ''early'' treatment has been described in previous studies, we defined our referent group (t 0 ) as treatment within the first twelve hours in order to represent those subjects who were most likely to have been inadequately resuscitated and in a state of occult hypoperfusion 10,25 .…”
Section: Treatment Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to provide clinically relevant categories for treatment beyond a simple dichotomy at twelve or twenty-four hours, we chose five time periods a priori on the basis of commonly used cut-points from the literature 14,15,24 : t 0 (twelve hours or less), t 1 (more than twelve hours to twenty-four hours), t 2 (more than twenty-four hours to fortyeight hours), t 3 (more than forty-eight hours to 120 hours), and t 4 (more than 120 hours). While twenty-four hours is the most commonly used threshold before which ''early'' treatment has been described in previous studies, we defined our referent group (t 0 ) as treatment within the first twelve hours in order to represent those subjects who were most likely to have been inadequately resuscitated and in a state of occult hypoperfusion 10,25 .…”
Section: Treatment Variablesmentioning
confidence: 99%
“…Other studies have suggested that internal fixation of long-bone fractures, either with intramedullary nailing or plate osteosynthesis, may have potentially deleterious effects in the acute setting, when systemic hypoperfusion 10 and inflammation [11][12][13] may increase susceptibility to end-organ injury and increase morbidity. A meta-analysis 14 demonstrated a large relative risk reduction (relative risk, 0.30; 95% confidence interval, 0.22 to 0.40) in respiratory complications in association with early operative fixation (usually within twenty-four hours), whereas two systematic reviews 15,16 demonstrated no difference in morbidity or mortality between early operative treatment (usually at less than twenty-four hours) and late operative treatment of femoral shaft fractures, either overall or within subgroups of patients with associated head injuries or thoracic injuries. These inconsistent findings have left clinicians debating what effect definitive fracture care has on adverse outcomes.…”
mentioning
confidence: 99%
“…Data from a randomized multicenter clinical trial indicated, that while in stable severely injured patients femoral nailing was associated with a shorter ventilation time, in borderline patients with increased risk of systemic complications it was associated with a higher incidence of lung dysfunction when compared to initial external fixation treatment [65]. However, an analysis of the literature indicated that from 63 controlled trials no generalized management strategy with respect to damage control orthopedics (DCO) could be provided and that the data from the German Trauma Registry Database were also inconclusive [66].…”
Section: Clinical Insightsmentioning
confidence: 99%
“…Koagulopathische Traumapatienten soll ten nach den Konzepten der "damage control surgery" behandelt werden [49,74,83]. Dabei wird die definitive anatomische Versorgung temporär zugunsten einer Sta bilisierung der lebensnotwendigen Physio logie zurückgestellt.…”
Section: Prophylaxe Und Therapieunclassified